Self-Concept Related to Stress in PLWHA - Jek Amidos Pardede; Cut Inten Balqis; Galvani Volta Simanjuntak (JENDELA NURSING JOURNAL, 2020)
Background: HIV / AIDS is an infectious disease that is very dangerous and deadly. So that the self-concept of HIV / AIDS patients sees themselves negatively and causes stress.Purpose: This study aims to determine the relationship between self-concept and stress in PLWHA.Methods: The design of this research is correlation analytic with a cross-sectional approach. The population of this study was all HIV / AIDS patients who were in Posyansus at RSUP H. Adam Malik Medan. The sampling technique was purposive sampling technique and obtained 39 patients. The data collection tool used a questionnaire that had been tested for validity and reliability, for the self-concept questionnaire as many as 15 statements with a value of r = 0.903 with a Cronbach's Alpha value of 0.914 and stress using the DASS 42 questionnaire consisting of 42 statements with a value of r = 0.916 with a Cronbach's Alpha value of 0.948 . The test used for data analysis was the Chi-Square test with a p-value 0.05.Results: The results showed that the majority of self-concept was positive (92.2%) and the majority of stress was mild (51.3%) and the p-value = 0.029 0.05.Conclusion: In conclusion, there is a significant relationship between self-concept and stress in PLWHA.